2021
DOI: 10.1007/s11356-021-15933-9
|View full text |Cite
|
Sign up to set email alerts
|

Why do Spanish households separate their e-waste for proper disposal? An econometric analysis

Abstract: Improving e-waste separate collection rates is of the utmost importance to achieve the environmental targets set in the Sustainable Development Goals. Therefore, this paper aims to identify the factors influencing the intentions of Spanish households to separate their e-waste for proper disposal. To this end, we carry out an econometric analysis revealing that the preoccupation with environmental issues is an endogenous regressor, so a bivariate model is required to avoid inconsistent results. The analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…First, many studies explored the influence of individual motivational factors on residents' WSB based on the theory of planned behavior and normative activation model [13][14][15]. The results showed that individual motivational factors, such as attitude toward waste separation, environmental concern, institutional trust, and awareness of consequences, positively affected residents' WSB [16][17][18]. However, a few scholars held a different view.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, many studies explored the influence of individual motivational factors on residents' WSB based on the theory of planned behavior and normative activation model [13][14][15]. The results showed that individual motivational factors, such as attitude toward waste separation, environmental concern, institutional trust, and awareness of consequences, positively affected residents' WSB [16][17][18]. However, a few scholars held a different view.…”
Section: Literature Reviewmentioning
confidence: 99%